Use of Intravascular Imaging During Chronic Total Occlusion Percutaneous Coronary Intervention: Insights From a Contemporary Multicenter Registry. Issue 8 (August 2016) - Karacsonyi, Judit; Alaswad, Khaldoon; Jaffer, Farouc A.; Yeh, Robert W.; Patel, Mitul; Bahadorani, John; Karatasakis, Aris; Danek, Barbara A.; Doing, Anthony; Grantham, J. Aaron; Karmpaliotis, Dimitri; Moses, Jeffrey W.; et al.
Abstract : Background: Intravascular imaging can facilitate chronic total occlusion (CTO) percutaneous coronary intervention. Methods and Results: We examined the frequency of use and outcomes of intravascular imaging among 619 CTO percutaneous coronary interventions performed between 2012 and 2015 at 7 US centers. Mean age was 65.4±10 years and 85% of the patients were men. Intravascular imaging was used in 38%: intravascular ultrasound in 36%, optical coherence tomography in 3%, and both in 1.45%. Intravascular imaging was used for stent sizing (26.3%), stent optimization (38.0%), and CTO crossing (35.7%, antegrade in 27.9%, and retrograde in 7.8%). Intravascular imaging to facilitate crossing was used more frequently in lesions with proximal cap ambiguity (49% versus 26%, P <0.0001) and with retrograde as compared with antegrade‐only cases (67% versus 31%, P <0.0001). Despite higher complexity (Japanese CTO score: 2.86±1.19 versus 2.43±1.19, P =0.001), cases in which imaging was used for crossing had similar technical and procedural success (92.8% versus 89.6%, P =0.302 and 90.1% versus 88.3%, P =0.588, respectively) and similar incidence of major cardiac adverse events (2.7% versus 3.2%, P =0.772). Use of intravascular imaging was associated with longer procedure (192 minutes [interquartile range 130, 255] versus 131 minutes [90, 192], P <0.0001) and fluoroscopy (71 minutes [44, 93] versus 39 minutes [25, 69], P <0.0001) time. Conclusions: Intravascular imaging is frequently performed during CTO percutaneous coronary intervention both for crossing and for stent selection/optimization. Despite its use in more complex lesion subsets, intravascular imaging was associated with similar rates of technical and procedural success for CTO percutaneous coronary intervention. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02061436.